Morbidity and mortality weekly report, Vol. 16, no. 13 Week ending April 1, 1967 - Communicable Disease Center (U.S.); United States Dept. of Health, Education, and Welfare Public Health Service; United States Bureau of Disease Prevention and Environmental Control
Cases of specified notifiable diseases: United States -- Notifiable diseases of low frequency -- Cases of specified notifiable diseases: United States for weeks ended April 1, 1967 and April 2, 1966 (13th week) -- Deaths in 122 United States cities for week ended April 1, 1967 -- Summary of reported cases of infectious syphilis Measles vaccine distribution Figure 1. Smallpox cases by week of report Dacca, Pakistan Table 2. Prevalence of beta hemolytic and group A streptococcus from school children in Nome, Alaska - Feb. 16-17, 1967 Epidemiologic notes and reports: Streptococcal infection - Nome, Alaska -- Reported cases of infectious syphilis International notes: Suspected smallpox - Honolulu, Hawaii -- Smallpox - Europe, India and Pakistan